Collection, conservation and distribution through the SMTA of samples of plant varieties protected by plant breeder's rights - Halewood, Michael (2012)
This document contains a question received by the Committee from one of its members during its third meeting in June 2012 and, at the invitation of the Commiittee, re-submitted in writing to the Secretariat. The document also provides some elements of analysis to facilitate the Committee’s appraisal.